Duration of oestrus, time of ovulation and progesterone profile in oestrus synchronized yak cows - BHUYAN, M; DEKA, B C; SARMAH, B C; CHAKRAVARTY, P; GOSWAMI, J; KHAN, M H (The Indian Journal of Animal Sciences, 2013)
Cyclic yak cows (24) of first to third lactation, maintained in yak farm, National Research Centre on Yak, Indian Council of Agricultural Research, Arunachal Pradesh, India were used for synchronization of oestrus using 3 different concentrations of progesterone in vaginal sponge. The duration of oestrus, time of ovulation and serum progesterone hormone levels during different days of intravaginal sponge implant and after insemination were recorded. In yak cows receiving 500, 600 and 700 mg of progesterone in vaginal sponge, the mean duration of oestrus was 25.76±1.07, 24.41±1.82 and 24.64±2.58 h and the time of ovulation after the end of oestrus was 11.6±0.90, 13.2±1.38, 12.6±1.25 h respectively. In control group out of 5 yaks one exhibited oestrus. The duration of oestrus and time of ovulation of that animal was 17.00 h and 16.00 h respectively. The difference between the treatment groups was not significant. The mean serum progesterone level at 3 days before implantation of intravaginal sponge varied from 1.50±0.38 to 3.97±1.15 ng/ml which increased gradually during the 14 days period of implantation and varied from 6.34±0.92 to 7.24±0.12 ng/ ml on 14th day. The serum progesterone level in yaks of treatment and control groups increased gradually from 0 day through 16 days after insemination. Thereafter it dropped in non-pregnant yaks but increased steadily in pregnant yaks.